Waiting for Good News : Living with Chronic and Serious Illness - Wilke, Sally, 1950- (Living with hope (Minneapolis, Minn.), 2018)
Support and wisdom when serious illness strikes, Sally Wilke gets it. She has lived with and through the serious chronic illness of someone she cared deeply about. And she has provided pastoral care to individuals and families in similar situations. Waiting for Good News captures her hard-won, helpful, and hope-filled wisdom. Wilke organizes this book around seven questions that those who face serious illness often ask. From "What Is the Diagnosis" to "Where Do I Find More Help?" she accompanies readers on their own journey. The heart of the book is the stories--Wilke's own, those of others who have struggled with severe illness, and accounts from the Bible. Here, readers will find strength, support, and a way forward in a difficult situation. As practical as she is wise, Wilke offers tools, tips, ideas, and resources for reflection and for obtaining additional support. Chapters conclude with questions that may be used for personal reflection and discussion with family members, patients, and support groups. Clergy, other pastoral-care providers, and family and friends of those who struggle with serious illness will find examples and helpful practices to guide their efforts as they partner with those seeking to find their way.